Teachers of Special Schools: Stressors and Manifestations of Occupational Stress - Kuvaeva, I (KnE Life Sciences, 2018)
Introduction. This article demonstrates the stress syndrome among teachers of special schools. There are two teaching techniques to pupils with physical and mental disorders: (1) in-class interaction and (2) distance computer interaction. We assume that teachers of special schools perceived a high level of occupational stress; the specific professional and organizational stressors explained the differences in stress syndromes among teachers of traditional (in class) and distance computer interaction. Method. Our study applies the IDICS system that analyzes the syndrome of occupational stress: stressors – subjective representations – acute and chronic stress manifestations – deterioration of stress (Leonova, 2006). The sample consists of 58 teachers (2 m./56 f.) of Russian special schools. Results. The findings have demonstrated that 29% participants perceived the high occupational stress and the ‘in class’ technique determines the most tension in work (p < 0.05). As the comparative analysis has proven, participants of traditional technique highlighted the stressful job conditions and chronic stress manifestations (aggression, depression, sleep disturbances) (p < 0.05). The teachers who work in a class, perceive the value of work tasks greater and experience the emotional stress on a higher level. Participants applying distance technique on the contrary distinguished extremely negative actual well-being (p < 0.05). Conclusion. Organization of work process determines the specification of stress syndrome among teachers in special schools. Practical relevance of the research lies in developing and implementing of stress-relieving program, targeting different groups of workers with account of traditional/distance technique. Keywords: occupational stress, stress syndrome, teacher, special school, ‘in-class’ technique, distance technique, disabled children